Software development by integrating the integrated using axiomatic design-lucas design for assembly (DFA) - Hamzanee, Mat Jusoh (2008)
In today competitive world, companies try to cut down the manufacturing cost and at the same time increase their profit .In order to be a competent player in the market, the product should arrive into market within a short time and reasonable price. This study is developing an intelligent computer based evaluation system for assembly by Integrating the integrated Axiomatic Design and Lucas DFA. The software is developed by using Microsoft Visual Basic 6.0. Through the concept of Axiomatic Design and Lucas DFA, it can be reduce the assembly cost at the early stage of the design phase and faster reach the market. However, there is a need of developing evaluation software regardless the technique or methods developed. The software that could simulate and evaluate the design virtually would reduce the product developing time. Thus the product could reach into the market dead in time. The objective of this paper is to present the framework for software development that integrating the integrated Axiomatic Design and Lucas DFA. The expected output is the evaluation software.